2017
DOI: 10.18203/issn.0019-5359.indianjmedsci20170483
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of hepatitis B and C infections among the healthcare workers despite low vaccination coverage for hepatitis B in Mumbai

Abstract: Background:The risk of acquiring hepatitis B virus (HBV) and hepatitis C virus (HCV) infections through exposure to blood or its products and contact with other body fluids is high amongst health care workers (HCWs). Despite potential risks, a proportion of HCWs never get vaccinated. This study aimed to investigate the vaccination practices and the prevalence of HBV infection in HCWs. Aims: To determine the prevalence of HBV and HCV, their possible association with occupational and non-occupational risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Among different groups of HCWs, doctors were found to have the highest vaccination percentage of 59.7% followed by students and nurses by 49.2% and 26%, respectively. This result is consistent with the study conducted in Mumbai in which the maximum vaccination rate was found in postgraduate residents followed by medical students [13]. This indicates the education level makes the difference; in other words, the higher the education level is, the more the awareness and the better the vaccination status will be.…”
Section: Discussionsupporting
confidence: 90%
“…Among different groups of HCWs, doctors were found to have the highest vaccination percentage of 59.7% followed by students and nurses by 49.2% and 26%, respectively. This result is consistent with the study conducted in Mumbai in which the maximum vaccination rate was found in postgraduate residents followed by medical students [13]. This indicates the education level makes the difference; in other words, the higher the education level is, the more the awareness and the better the vaccination status will be.…”
Section: Discussionsupporting
confidence: 90%
“…It was more than that of another study conducted in Pakistan having a prevalence of 4.13% among HCPs [ 8 ]. It was even more than the prevalence of HCV among HCPs as shown by a study conducted in India [ 9 ]. This difference is because the HCPs adopt better preventive measures in tertiary health-care centers.…”
Section: Discussionmentioning
confidence: 99%
“…It is closer to the results of ALHaj et al ., (2019) and Ansari and Dixit (2017) studies that conducted in Yemen (4.17%) and India (4%) among HCWs, respectively. However, it was more than the prevalence of HCV among HCWs in Dhaka-Bangladesh, Poland and India (1% and 1.9% and 3%, respectively) (Shah et al ., 2017). This difference is because the HCWs adopt different preventive degree measures in different health-care centers.…”
Section: Discussionmentioning
confidence: 99%